The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1057/mel.2013.2
|View full text |Cite
|
Sign up to set email alerts
|

Slow steaming impacts on ocean carriers and shippers

Abstract: A b s t r a c t Ocean container carriers have implemented slow steaming (reduced vesselspeeds) in recent years to improve fuel efficiency and lower greenhouse gas emissions. However, many shippers oppose the practice due to increased pipeline inventory associated with longer transit times. Given this conflict, this article seeks to quantify the costs and benefits of slow steaming relative to carriers and shippers. We simulate a high volume AsiaNorth America container trade lane to estimate slow steaming impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 24 publications
4
50
0
1
Order By: Relevance
“…Notwithstanding the positive environmental and economic effects of slow-steaming, the practice also entails significant and potentially negative operational and economic consequences for the shippers, i.e., the customers of the service that the shipping companies produce-most notably, the increased lead time resulting from longer transport times (Fredriksson & Jonsson, 2009;Maloni et al, 2013;McKinnon, 2012). Unilateral changes in sailing speed contribute positively to the reduction of CO 2 emissions, but only temporarily if the supply chains using the service cannot cope with the lead times and opt for more carbon intensive alternatives.…”
Section: Slow-steaming and Its Effects On Logisticsmentioning
confidence: 99%
“…Notwithstanding the positive environmental and economic effects of slow-steaming, the practice also entails significant and potentially negative operational and economic consequences for the shippers, i.e., the customers of the service that the shipping companies produce-most notably, the increased lead time resulting from longer transport times (Fredriksson & Jonsson, 2009;Maloni et al, 2013;McKinnon, 2012). Unilateral changes in sailing speed contribute positively to the reduction of CO 2 emissions, but only temporarily if the supply chains using the service cannot cope with the lead times and opt for more carbon intensive alternatives.…”
Section: Slow-steaming and Its Effects On Logisticsmentioning
confidence: 99%
“…Early studies from North Americ a considered cost as the most important because shippers were int erested in reducing logistic operational costs (Brooks, 1985;Gibson et al, 2002;Murphy and Daley, 1995). However, recent studies from North America have discovered that service relat ed factors (that is, transit time, quality service, on -time delivery performance) have become more important (BenAkiva et al, 2013;Maloni et al, 2013;Zsidisin et al, 2007).…”
Section: Carrier Selection Criteria From One Country's Perspectivementioning
confidence: 99%
“…Voss et al (2006) analysed the significant factors that drove transport service buyers when selecting ocean carrier and found that delivery reliability, rates charged, and carrier reputation were the three most important factors taken into consideration by shippers. Additionally, Saldanha et al (2009) Gibson et al (2002) Cost, effectiveness, trust, flexibility US Zsidisin et al (2007) On-time delivery performance US Premeaux (2010) Flexible rates, response to emergency, IT US Ben-Akiva et al (2013) Quality service and total logistics costs US Maloni et al (2013) Transit time, Co2 reduction operations US/Asia Gailus and Jahn (2013) Reliability, transit time Germany Kannan et al (2011) Low rate, pricing flexibility and flexibility India Van den Berg and de Langwn (2014) Cost driven Netherlands Lam and Zhang (2014) Cost control, reliability and responsiveness Singapore Harrision and Fichtinger (2013) Time, schedule, transit time and frequency UK transit time and transit time reliability as the most critical factors which influenced the decision making of freight service buyers when selecting ocean container carrier.…”
Section: Carrier Selection Criteria From One Country's Perspectivementioning
confidence: 99%
“…e) The adoption of 'slow steaming' by container shipping lines, primarily to cut bunker fuel costs. To compensate for the lengthening of transit-times on the maritime leg, shippers are keen to accelerate hinterland transport and improve its reliability to minimise adverse effects on production and distribution schedules (Maloni et al, 2013). f) The shift in the balance of costs between deep-sea and hinterland transport.…”
Section: Road Investment and Congestion Managementmentioning
confidence: 99%